(untitled) (Educação e Pesquisa, 2002)
The article analyzes the results verified in the main disciplines (Mathematics and Spanish) in the Chilean Quality of Education Assessment System (SIMCE) in 2000 for the 8th grade of the elementary school. Firstly, the general aspects of the results are examined, and then they are compared on the basis of the socioeconomic level of the schools. The various groups of information collected confirm that the socioeconomic variable is the determinant factor in the results, and that the school affiliation (private, public or state funded) loses importance. When checked against the cost of school fees (direct cost), the efficiency of results favors the schools that serve the more vulnerable population. In that respect, two aspects are of relevance: first, the municipal schools are efficient to the poorer layers of the population; second, at the socioeconomic levels where there is total competence (the market works), the dependence on the school is secondary, the socioeconomic level being the dominant explaining factor. Comparison of schools by socioeconomic group and affiliation eliminates an inequality factor that has effect on the performance results: the school equipment and infrastructure, if considered in a fictitious situation (equality of basic processes), favor the better equipped schools, which incorporate funding from the parents. This casts doubt on the assertion that differences intra-socioeconomic group are due to the school management variables; the evidence is compelling when the socioeconomic level is incorporated as an explaining variable.